2007
DOI: 10.1111/j.1365-2222.2007.02893.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral allergy syndrome and anaphylactic reactions in BALB/c mice caused by soybean glycinin and β‐conglycinin

Abstract: Soybean-specific IgE and IgG1 antibodies increased, with high levels of histamine release, severe degranulation of mast cells and damage of the epithelium of small intestine in mice sensitized with glycinin and beta-conglyinin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 40 publications
4
42
0
2
Order By: Relevance
“…Recently, the sensitizing and anaphylactic potential of the soybean major storage proteins was demonstrated in an animal model with BALB/c mice sensitized and challenged with purified natural Gly m 5 and Gly m 6. 31 By contrast, only 4 of 12 (33%) study subjects who experienced mild subjective symptoms had IgE specific for the soybean major storage proteins. However, 11 (92%) of the subjects who experienced mild subjective symptoms had specific IgE to the birch pollen-related soy allergen Gly m 4.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, the sensitizing and anaphylactic potential of the soybean major storage proteins was demonstrated in an animal model with BALB/c mice sensitized and challenged with purified natural Gly m 5 and Gly m 6. 31 By contrast, only 4 of 12 (33%) study subjects who experienced mild subjective symptoms had IgE specific for the soybean major storage proteins. However, 11 (92%) of the subjects who experienced mild subjective symptoms had specific IgE to the birch pollen-related soy allergen Gly m 4.…”
Section: Discussionmentioning
confidence: 90%
“…Increased plasma D-lactic acid levels reflect changes in intestinal permeability (Liu et al 2008b). DAO is an enzyme that serves as an indicator of intestinal epithelial integrity: when the intestinal mucosa is damaged, serum DOA levels increase (Chang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this situation, we noted acute hypotension and tachycardia in this mouse model as well suggesting similarity of the food induced severe reactions in both species. There are two previous studies reporting changes in cardiovascular functions in mouse models of food allergy: (i) Ganeshan et al 2009 reported acute hypotension responses and tachycardia in a staphylococcus exotoxin adjuvant based mouse model of ovalbumin allergy; and (ii) Liu et al (2008) reported hypotension responses in a soybean allergy mouse model. Here, we expand these findings further by providing evidence for acute cardiovascular dysfunction upon oral elicitation of reactions in an adjuvant-free tree nut allergy mouse model.…”
Section: Discussionmentioning
confidence: 96%